2014
DOI: 10.1016/j.mee.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of Ag/Ta and Ag/TaN thin-films

Abstract: a b s t r a c tAlthough wide band gap devices (WBG, e.g. GaN and SiC) are eminently suitable for high temperatures and harsh environments, these properties cannot be fully taken advantage of without an appropriate interconnect metallization. In this context, silver shows promise for interconnections at high temperatures. In this work, the thermal stability of Ag with two barrier metals -Ta and TaN -was therefore investigated. Metal stacks, consisting of 100 nm of silver on 45 nm of either Ta or TaN were sputte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…For example, Ag/GaN multilayer films are used as the conductor electrodes of lightemitting diodes (LEDs), the coatings of laser safety glasses, and display window materials which block microwave radiation [4,5]. Ag/TiN or Ag/TaN multilayer films are potential materials to be used as interconnects on integrated circuits [6][7][8]. Beyond that, Ag/TiN multilayer films are also used in the photocatalytic field [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ag/GaN multilayer films are used as the conductor electrodes of lightemitting diodes (LEDs), the coatings of laser safety glasses, and display window materials which block microwave radiation [4,5]. Ag/TiN or Ag/TaN multilayer films are potential materials to be used as interconnects on integrated circuits [6][7][8]. Beyond that, Ag/TiN multilayer films are also used in the photocatalytic field [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Pt has better electromigration properties than Al at high temperatures, but instead suffered from poor step coverage since it was evaporated [10]. Ag and Cu were tested separately as interconnect material, but not in the integrated circuit process [46][47][48].…”
Section: Process Technology Designmentioning
confidence: 99%
“…Some separate tests have been made on Ag and Cu metallization for SiC integrated circuits. However, the proper use of capping layers of Ta or TaN is critical for both metal systems for use above 600 °C [46][47][48].…”
Section: Metal and Dielectricsmentioning
confidence: 99%
“…Se ha reportado que el tratamiento térmico mejora la cristalización de las películas metálicas de Ni, Au y Cu cambiando la morfología superficial de estas [6][7][8]. Además se han reportado cambios en la morfología superficial de las películas delgadas de Ag con la adición de impurezas de Cu [9] y después de un recocido térmico [10]. Con el tratamiento térmico se puede conseguir mejorar la cristalización de películas delgadas y mejorar sus propiedades físicas, tales como la adhesión, la conductividad eléctrica, incrementando de esta forma sus potenciales aplicaciones.…”
unclassified